2015
DOI: 10.1007/s11695-015-1986-y
|View full text |Cite
|
Sign up to set email alerts
|

Staple Line Bleeding in Sleeve Gastrectomy—a Simple and Cost-Effective Solution

Abstract: Intraoperative prophylactic tranexemic acid use is a simple and economical option for effectively reducing staple line bleeds leading to significant decrease in operating times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
2
47
2
1
Order By: Relevance
“…Choosing the appropriate length of staples is believed to play some role in the prevention of this complication [30]. A study by Chakravartty et al reports that tranexamic acid could be an additional, simple, and cost-effective method for prophylaxis of staple line bleeding [31]. Possible methods for managing the bleeding during an operation include compression, ligation, clipping, and suturing [32].…”
Section: Discussionmentioning
confidence: 99%
“…Choosing the appropriate length of staples is believed to play some role in the prevention of this complication [30]. A study by Chakravartty et al reports that tranexamic acid could be an additional, simple, and cost-effective method for prophylaxis of staple line bleeding [31]. Possible methods for managing the bleeding during an operation include compression, ligation, clipping, and suturing [32].…”
Section: Discussionmentioning
confidence: 99%
“…Presumably clinicians are reluctant to use this medicine in fear of causing thromboembolic complications and rather reoperate to reach hemostasis. Chakravarrty et al, studied the effect of intraoperative tranexamic acid on staple line bleeding, and found that intraoperative prophylactic tranexamic acid use effectively reduces staple line bleeding [ 14 ]. Another study describes their positive experience with tranexamic acid use for reducing staple line bleeding [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of tranexamic acid against staple line bleeding in sleeve gastrectomy has been studied [ 14 , 15 ]. In our hospital, over 500 bariatric procedures are performed annually.…”
Section: Introductionmentioning
confidence: 99%
“… 39 The use of tranexamic acid as a routine intraoperative method of reducing hemorrhage has been proposed. 40 …”
Section: Discussionmentioning
confidence: 99%